2020
DOI: 10.3233/jpd-202035
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Architecture and Design in the Management of Parkinson’s Disease: A Systematic Review

Abstract: Background: Parkinson’s disease (PD) is a neurological condition characterized by the development of daily disabling symptoms. Although the architecture and design of a PD patient’s environment can hinder or facilitate full participation in daily activities, their putative role in the management of these patients has received little attention to date. Objective: We conducted a systematic review to evaluate the evidence of architectural and design features in the management of people with PD. Methods: An electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…Published shortly after the search period for our review, a systematic review of the role of architecture and design in the management of PD caught our interest. 38 In that context the built and natural environment dimension seems to be more prominent than in the publications with a specific focus on housing included in the present review. Ramos et al show that design features such as pavement characteristics in terms of unstable surfaces and level differences are major causes of falling.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Published shortly after the search period for our review, a systematic review of the role of architecture and design in the management of PD caught our interest. 38 In that context the built and natural environment dimension seems to be more prominent than in the publications with a specific focus on housing included in the present review. Ramos et al show that design features such as pavement characteristics in terms of unstable surfaces and level differences are major causes of falling.…”
Section: Discussionmentioning
confidence: 91%
“…Going beyond the specific focus on housing, there is PD research focusing on the built and natural environment dimension in a broader sense, which was out of the scope of the present study. Published shortly after the search period for our review, a systematic review of the role of architecture and design in the management of PD caught our interest 38 . In that context the built and natural environment dimension seems to be more prominent than in the publications with a specific focus on housing included in the present review.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results strengthen their hypothesis that the environmental factors (ability to drive [22], caregiving [22]), the personal factors (sex [22], age [6,22]), the body function (cognitive impairment [6], postural instability [6]), and "social participation" [22] are determinants of patient-reported functional mobility. Furthermore, according to the recent review of Ramos, et al [35], architecture and design (e.g., housing adaptations/accessibility/usability, floor surface/lights/signaled pedestrian crossings or reaching/space between objects) are associated with functional mobility. However, the included studies of that review applied qualitative study designs [36,37] or did not assess patient-reported functional mobility [38].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, most of the conducted studies concentrate on disabilities and problematic areas, such as the built environment for vulnerable members of society or people with particular diseases such as Alzheimer's, Parkinson's, and dementia (e.g., Refs. [66,[115][116][117][118][119][120][121][122][123][124][125][126]). Yet, the impacts of conventional construction systems (CCSs) and conventional construction materials (CCMs) on health (i.e., physical and mental WB) are rarely discussed.…”
Section: Health and Housingmentioning
confidence: 99%